Desafios para implementação da cobrança pelo uso dos recursos hídricos de domínio do Estado de Roraima - Araújo, Deusdedith Ferreira (2023)
The state of Roraima, although it is one of the states in the federation with the greatest water abundance, its use has been made without the proper application of management instruments. In this context, the present research has as its theme the analysis of the challenges for the implementation of charging for the use of water resources in the domain of the state of Roraima. The aim is to list the impediments to charging for the use of water resources in the domain of the state of Roraima. To this end, a bibliographical research was carried out on charging for the use of water resources in Brazil and abroad. Added to this, a systematic review of the literature was carried out in an attempt to find other texts that have already discussed this subject. An exploratory-qualitative research was established as a methodology for this investigation, which is divided into three main phases: a) a bibliographical research added to a systematic review of the literature; b) field research in documentary format applied to the National Water and Sanitation Agency (ANA) and the State Foundation for the Environment and Water Resources of Roraima (FEMARH), added to this an informal conversation with two directors of FEMARH and; c) the elaboration of a draft of a government decree that deals with the criteria and parameters for charging for the use of water resources in the domain of the State of Roraima, as the Final Product of this dissertation. Eight factors that impede charging for water use in the state of Roraima were identified: a) Lack of Criteria and Parameters, b) Political and cultural issues, c) Water crisis and organization of residents, d) Absence of trained professionals, e) The transfer of the charge to the consumer, f) Creation of a state basin committee, g) Specific state legislation, h) Reorganization of FEMARH. It was concluded that the impediments are correlated with each other and when implementing the charge it is possible that more will arise, but that the implementation of the charge for the use of water resources in Roraima is necessary and urgent since its absence implies in the perpetuation of the problems of management and, moreover, it is a state with enormous water wealth that requires, therefore, a strong stimulus for its conservation in quality and quantity for present and future generations.